Moving forward through feeding back: a case study of assessment feedback in higher education - Turnbull, Alison (2022)
This thesis examines the complex contexts and relationships around assessment feedback in higher education. Firstly, it examines tutors’ experiences and reflections around the evolution of their assessment feedback practices in a changing landscape. Secondly, and based on the premise that contextual change can contribute to feedback dissonance, the thesis examines tutors’ and students’ experiences of the practical, pedagogic, and socio-affective dimensions of using audio-visual feedback technology to achieve feedback resonance. Findings show that tutors experience professional tensions between their feedback values and practice, and that audio-visual feedback technology can offer practical affordances, as well as a different pedagogic and socio-affective feedback experience. Students particularly welcomed the relational dimensions of the audio-visual medium and asserted positive impacts on their feedback engagement. They also reported practical challenges in the forms of additional time investment, navigational difficulty, and language accommodation. The research adds to the limited literature around tutors’ feedback practice experiences, and makes a contribution to knowledge at the theoretical level by re-framing the work of Tuck (2012) in relation to tutors’ feedback roles. At the practice level, the research contributes to knowledge around the uses of audio-visual feedback technology at both the pedagogic and socio-affective levels. The research extends knowledge in relation to international students’ feedback engagement, and the potential of the audio-visual medium to mediate affective feedback response and to stimulate subsequent dialogue of a pedagogic and pastoral nature between tutors and students. The findings are significant in that they offer a response to growing feedback demands which can threaten tutor well-being, as well as exploring the pedagogic and socio-affective affordances of screencasting to build feedback resonance and reverberation.